2018
DOI: 10.4103/jpn.jpn_100_17
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal anomalies in early onset scoliosis: Current concepts

Abstract: Early onset scoliosis (EOS) is deformity of the spine below the age of 5 years. Children with EOS are at risk of impaired thoracic cage development and pulmonary maturation. Initial evaluation consists of determining the etiological cause for EOS, i.e., congenital, neurogenic, idiopathic, or syndromic. The advent of magnetic resonance imaging in recent times has lead to increased awareness of neurogenic causes leading to EOS. Evaluation of spinal cord anomalies in EOS is very important as early diagnosis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…The overall incidence of intraspinal abnormalities reported in patients with congenital spinal deformity is 37%, ranging from 21% to 43%. [1][2][3][4][5][16][17][18] Similarly, Williams et al 11 reported that patients with Congenital-EOS had higher odds of abnormal MRI findings than other EOS categories. Specifically, they found a 24% prevalence of overall abnormal findings in the general EOS population with 35% in the congenital group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall incidence of intraspinal abnormalities reported in patients with congenital spinal deformity is 37%, ranging from 21% to 43%. [1][2][3][4][5][16][17][18] Similarly, Williams et al 11 reported that patients with Congenital-EOS had higher odds of abnormal MRI findings than other EOS categories. Specifically, they found a 24% prevalence of overall abnormal findings in the general EOS population with 35% in the congenital group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have analyzed the correlation between Congenital-EOS and MRI underlying pathology. The overall incidence of intraspinal abnormalities reported in patients with congenital spinal deformity is 37%, ranging from 21% to 43% 1–5,16–18 . Similarly, Williams et al 11 reported that patients with Congenital-EOS had higher odds of abnormal MRI findings than other EOS categories.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 , 24 , 25 ]Formatting... please wait Similarly, in cases of congenital scoliosis, early-onset scoliotic deformity may occur in 25–80% of patients with DM, TC, or SM, often with Chiari malformation. [ 16 , 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention is pivotal in managing diastematomyelia, addressing neurological symptoms, preventing further complications, and improving the patient's overall quality of life [5]. Laminectomy and correction of the split spinal cord, as performed in this case, represent established surgical techniques for managing this complex anomaly [6]. This case report aims to contribute to the existing literature on the clinical presentation, diagnostic approach, and successful surgical management of type 2 diastematomyelia with spina bifida in a pediatric patient.…”
Section: Introductionmentioning
confidence: 93%